Move Analysis of the English Bachelor Thesis Abstracts Written by Indonesians - Fitri Budi Suryani; Rismiyanto Rismiyanto (Prominent, 2019)
Due to the global era, bachelor thesis abstracts written by non-native English speakers (Indonesians) from non-English departments in Indonesia are usually written in two languages, i.e. Indonesian and English. The English bachelor thesis abstracts are mostly the translated ones from Indonesian and do not always follow the features of abstract genre. This study aims  at examining the rhetorical moves of English bachelor thesis abstracts written by students from non-English departments. The data consisted of twenty abstracts selected randomly from hard and social science departments of Universitas Muria Kudus. The analysis employed Hyland’s five rhetorical move model. The study reveals that most English bachelor thesis abstracts did not follow the five rhetorical moves. The absence of some rhetorical moves in the English bachelor thesis abstracts may lead to the communicative purposes not achieved and thus might cause difficulty for readers to understand the study.Keywords: move, English bachelor thesis abstract, Indonesians